"Because migration begins from the villages": environmental change within the narrations of the Ewe diaspora. Issue 16 (10th December 2020) - Hillmann, Felicitas; Okine, Rueben Korley; Borri, Giulia
ABSTRACT: The article analyses the role of environmental change within the narrations of the Ewe-diaspora, a sub-group of the Ghanaian diaspora. It focusses on the role and the impact of the diaspora when it comes to coping with environmental change at the place of origin. It highlights the nexus with international migration.